Pengaruh Ukuran Perusahaan, Kebijakan Dividen, Kinerja Keuangan dan Konvergensi IFRS Perusahaan terhadap Tindakan Income Smoothing pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Saadatut Azizi Doraini; Seto Sulaksono Adi Wibowo (Journal of Applied Accounting and Taxation, 2017)
Earnings information is a component of the company's financial statements are intended to assess the performance of the company. Investors' attention is often focused only on information provided by the company profits. It can give an opportunity for management to take action income smoothing (income smoothing). In this cas, the selected variables are size, dividend payout ratio, return on asset financial leverage, net profit margin and IFRS convergence. The statistical method used is logistic regression in service companies listed in Indonesia Stock Exchange in 2010 through 2013.These results indicate that the variable size of the company, financial leverage, net profit margin significantly positive influence. Inversely variable dividend payout ratio and the company's profitability significantly negative influenc and convergence of IFRS variable has no effect on income smoothing. Key Words: income smoothing, firm size, dividend payout ratio, return on assets, international financial reporting standards, financial leverage, and net profit margin.